Pengaruh Kepemimpinan, Motivasi, dan Pengawasan terhadap Tingkat Disiplin Kerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Cilacap - Febrika Indriani Saputri; Tri Harsini Wahyuningsih (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
This study aims to analyze the influence of leadership, motivation, and supervision on the level of work discipline of the Cilacap Regency Population and Civil Registration Office. The sample was taken using purposive sampling with the criteria of employees who have worked for more than 2 (two) years, as many as 86 people. Data analysis used multiple linear regression. Partial research results show that leadership has a positive effect (0.266) and significant (0.001) on the level of employee work discipline, motivation has a positive effect (0.160) and significant (0.022) to the level of employee discipline and supervision has a positive effect (0.050) and not significant (0.470) on the level of employee work discipline. Thus, it means that leadership has an effect on work discipline, motivation has an effect on work discipline, and supervision has no effect on work discipline for employees at the Department of Population and Civil Registration of Cilacap Regency.